What Can Queer Theory Do for Intersex? - Morland, Iain (GLQ: A Journal of Lesbian and Gay Studies, 2009)
In this essay I explore how queer theory might account for postsurgical intersex bodies of diminished genital tactility. In other words, I evaluate whether a critique of surgery’s effects is possible from a queer theoretical perspective on the body. I contend that for this purpose queer theory must do more than focus on bodily sensations such as pleasure, shame, and touching. The essay makes four key claims: first, that the desensitized postsurgical body cannot be accounted for by a queer discourse in which sexual pleasure is a form of hedonistic activism; second, that a queer discourse of shame enables a degree of critical engagement with the surgical creation of atypically sensate bodies; third, that pleasure and shame are both queer sensations, and queer theory’s assumption of a sensorial basis to cultural critique, which is exemplified by the queer touch, flounders when confronted with the desensitized intersex body; fourth, that if queer theory is figured as a kind of reaching—but not necessarily touching—then it can be of greater use in accounting for the problematic yet ambivalent effects of intersex surgery.
Keywords: LGBTQIA2+; approches et analyses; arts; care; corps; cours; discipline; identités LGBTQIA2+; intersexuation; lit4700; premier cycle; queer; ressource en ligne; thématiques; études culturelles; études littéraires

Les subalternes peuvent-elles parler? - Spivak, Gayatri Chakravorty..; Vidal, Jérôme.. (Éd. Amsterdam, 2009)
Dans le cadre d'un dialogue critique avec Michel Foucault, Gilles Deleuze et la tradition marxiste, G.C. Spivak articule le concept de subalterne (à ne pas confondre avec les notions de minoritaire ou d'opprimé) et s'interroge sur les femmes subalternes du tiers-monde, l'unification des subalternes au sein d'une communauté.
Keywords: approches et analyses; arts; care; com5170; corps; cours; discipline; féminisme décolonial; har4600; histoire et politique; incontournable; oui; premier cycle; thématiques; études littéraires; études postcoloniales